Electrochemical chiral amino acid biosensor based on dopamine-localized gold nanoparticles @ left-handed spiral chiral carbon nanotubes. Issue 31 (27th July 2020) - Lu, Haijun; Wang, Zimeng; Fan, Xinyu; Wang, Haiyang; Zhang, Qi; Fu, Mingxuan; Ning, Guyang; Zhang, Yufan; Wang, Huan
Abstract : Preparation of dopamine-localized gold nanoparticles @ left-handed spiral chiral carbon nanotubes (HLCNT-AuNPs-2) and the chiral separation of tyrosine (Tyr) and tryptophan (Trp). Abstract : The high electrocatalytic performance plays a decisive role in the efficient electrochemical sensing of electrocatalysts. A spiral chiral carbon tube (HLCNT) loaded with gold nanoparticles (AuNPs) was prepared by electrochemical methods. Dopamine was first electropolymerized on the surface of the HLCNT, and then it acted as a localizer to uniformly load the AuNPs onto the surface of the HLCNT. The dopamine-localized gold nanoparticles @ left-handed spiral chiral carbon nanotubes (HLCNT-AuNPs-2) material combined the chiral structure of chiral carbon nanotubes and the high conductivity of AuNPs. The HLCNT-AuNPs-2 realized the qualitative and quantitative detection of tyrosine (Tyr) and tryptophan (Trp) isomers by their different oxidation potentials and current signals. Through quantitative detection, the analytical results showed that the detection limit of l -Trp was calculated to be 5.31 μM, and the detection limit of l -Tyr was 9.04 μM. More importantly, the material realized the real sample detection of amino acids, which is of great significance for the practical detection of amino acid isomers in medicine and biology.